Realitas Sosial Perempuan Bercadar : Penolakan Dan Penerimaan di Masyarakat Sumbersari Kabupaten Jember - Galuh Putri Rahayu; Ida Tri Widiyaningsih; Alina Ratna Anjali (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Each religion has its own symbols and uniqueness. Islam is the dominant religion in Indonesia. Islamic women are usually symbolized by the hijab and long clothes. Not infrequently there are also Muslim women who wear the veil. The veil is a face covering for Muslim women that covers all parts of the face except for the eye area, which is combined with a hijab and long clothes which are usually dominated by dark colors. But in Indonesia itself, women who wear the veil reap many pros and cons. This research was conducted to find out how the interactions that occur between women who wear the veil and the surrounding community. This study uses a type of qualitative research with an ethnographic approach. Qualitative research helps researchers to obtain an answer to a symptom, fact or reality that is being faced and to be able to understand a problem that is being studied. Ethnography is the study of culturally shared groups involving the core values and beliefs of their members. The subjects of this study were students studying at several campuses in Jember Regency. The results showed that the motivation of the informants in wearing the veil was as a form of obedience to religion and also to protect and avoid bad things. Several informants stated that they experienced some difficulties in interacting with the surrounding community when they wore the veil. Not infrequently they also receive negative stigma from society. So this is also a big challenge for veiled women in Indonesia, especially in the area around Jember Regency.